Mechanism of tonifying-kidney Chinese herbal medicine in the treatment of chronic heart failure - Chen, Lizhen; Yu, Dayun; Ling, Shuang; Xu, Jin-Wen (Frontiers in Cardiovascular Medicine, 2022)
According to traditional Chinese medicine (TCM), chronic heart failure has the basic pathological characteristics of "heart-kidney yang deficiency". Chronic heart failure with heart- and kidney-Yang deficiency has good overlap with New York Heart Association (NYHA) classes Ⅲ and Ⅳ. TCM classical prescriptions for the treatment of chronic heart failure often take "warming and tonifying kidney-Yang" as the core, supplementing herbal compositions with functions such as "promoting blood circulation and dispersing blood stasis". Nowadays, there are still many classical and folk prescriptions for chronic heart failure treatment, such as Jinkui Shenqi pill, Zhenwu decoction, Bushen Huoxue decoction, Shenfu decoction, Sini decoction, as well as Qili Qiangxin capsule. In this review, we summarized and elaborated the functions and mechanisms of various classic prescriptions and their herbal active ingredients from the perspective of modern pharmacology. Chinese prescriptions and the active compounds played a pivotal role in cardiac hypertrophy, vasodilation and fibrosis by inhibiting inflammation, regulating immune and neurohumoral factors. Simultaneously, their regulations of metabolic reprogramming in chronic heart failure, such as glycolysis and lipid β-oxidation, were also expounded. Briefly, this article is expected to provide a modern pharmacological interpretation of the role and mechanism of traditional Chinese medicine in the treatment of chronic heart failure.